2017
DOI: 10.1111/anu.12502
|View full text |Cite
|
Sign up to set email alerts
|

Beef tallow is suitable as a primary lipid source in juvenile Florida pompano feeds

Abstract: It is assumed that Florida pompano have dietary EPA (20:5n-3) and DHA (22:6n-3) requirements. However, it is unclear whether both are equally important in meeting demand for n-3 long-chain polyunsaturated fatty acids (LC-PUFAs) or whether the requirement(s) can be influenced by other fatty acids. Accordingly, we assessed production performance and tissue composition of juvenile Florida pompano (41.0 ± 0.5 g) fed diets containing fish oil; beef tallow; or beef tallow partially or fully supplemented with EPA, DH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 39 publications
3
22
0
Order By: Relevance
“…Our results also show the importance of DHA supplementation in BT-based diets on enhancing growth performance and feed utilization and ensuring the desired levels of DHA in the whole fish. Similar results were also reported in a previous study conducted on Florida pompano, Trachinotus carolinus, showing that fish fed the DHA-supplemented feeds that replaced FO with BT exhibited the best performance in growth among the tested feeds (Rombenso, Trushenki, & Schwarz, 2017).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our results also show the importance of DHA supplementation in BT-based diets on enhancing growth performance and feed utilization and ensuring the desired levels of DHA in the whole fish. Similar results were also reported in a previous study conducted on Florida pompano, Trachinotus carolinus, showing that fish fed the DHA-supplemented feeds that replaced FO with BT exhibited the best performance in growth among the tested feeds (Rombenso, Trushenki, & Schwarz, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…Similar findings were also observed in the subadult olive flounder fed diets containing different lipid sources and levels (Kim et al, 2012). This can be supported by findings in other fish species such as Florida pompano and Atlantic salmon showing that the total lipid content of fillet was not affected by the replacement of FO with BT (Emery et al, 2014;Rombenso et al, 2017). In this study, it was demonstrated that the growth performance, whole-body nutrient composition, and plasma parameters were largely unaffected by the lipid substitution; however, the fatty acid profile of whole fish was altered.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…With the expected wide adoption of cobia pelleted and extruded feeds, the next step in improvements to the sustainable expansion of cobia culture in Brazil, embraces lowering fishmeal and fish oil content by adopting alternative proteins and lipid sources, including soybean meal and oil, rapeseed oil, palm oil, poultry-by meal and fat, pork lard, beef tallow among other animal or plant ingredients, with proven suitability without production nor nutritional impairment (Betancor et al, 2016;Rombenso et al, 2017;Suarez et al, 2013;Trushenski et al, 2012;Watson et al, 2014;Woitel et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Rendered beef tallow has been used alone or in addition to EPA, DHA or EPA + DHA to partially or completely replace FO in aquafeeds for Florida pompano of 41 average initial weight (Rombenso et al . ). Fish meal provided half of the dietary protein in all of the experimental diets.…”
Section: Strategies For Sustainable Tropical Aquaculture: Feed Ingredmentioning
confidence: 97%